Penerapan Algoritma K-Means Pada Penyebaran Covid-19 Di Provinsi Jambi - Reza Pahlevi; Muhammad Wahyu Prayogi; Errissya Rasywir; Yovi Pratama (Journal of Computer System and Informatics (JoSYC), 2022)
The purpose of this study using the K-Means Cluster method is to determine the level of distribution of Covid-19 cases in the high, medium, and low categories in each region in Jambi Province. There are several aspects that can be measured such as population, population density, positive cases infected with Covid-19, recovered patients, and patients who died. The data collection method used is the documentation method in the form of secondary data obtained from the Jambi Provincial Government website. The data used were positive, recovered, and died and were analyzed using the WEKA application. From the results of research with the K-Means method using 3 clusters. Cluster 0 is a cluster with a high level of distribution category, which is in the city of Jambi. Cluster 1 is a cluster with a medium level distribution category consisting of Batanghari, Merangin, Muaro Jambi, Tanjab Timur. Cluster 2 is a cluster with a low-level distribution category consisting of Bungo, Kerinci, Sarolangun, Sungai Penuh, Tanjab Barat, Tebo.